Learning from the Botton Up (2016)
National housing policies are often limited by the need to implement structural change. In 1997, urban reform laws in Colombia created decentralized municipal, administrative, and political systems; since then, local governments have acquired planning, fiscal, and administrative autonomy, and are administered by elected councils and mayors. Municipalities emerged as key players for introducing land policy and planning changes to buttress the low-income housing supply and also to directly upgrade slums. Colombia is a good example of a country in the Latin America and Caribbean (LAC) region where municipalities have stepped into the void that was left by national policies and it has taken the lead in terms of housing. Bogota and Medellin have had successful experiences with low-income hous - ing policy. With strong institutions, financial muscle, and favorable political envi - ronments, these two cities present noteworthy examples of innovative territorial approaches and advantages of urban reform law in force that includes planning instruments that serve as a platform for policies that relate to large-scale, inte - grated, and low-income housing; slum upgrading; and land issues. Limited to the two cities, the experiences, unfortunately, did not evolve into national policies.